Chemically specific termination control of oxide interfaces via layer-by-layer mean inner potential engineering - H. Y. Sun (Nature Portfolio, 2018)
Precisely controlled growth of oxide interfaces at the atomic layer level is critical for device applications but quite challenging. Here Sun et al. show real time monitoring and control of the surface composition of epitaxial strontium titanate perovskite films by analysing the Kikuchi lines.